T cell metabolism in homeostasis and cancer immunity. (April 2021) - Wei, Jun; Zheng, Wenting; Chapman, Nicole M; Geiger, Terrence L; Chi, Hongbo
Highlights: Cell-intrinsic and cell-extrinsic factors influence the metabolic state of T cells. Glucose and mitochondrial metabolism regulate antitumor activity of T cells. Targeting Treg cell metabolism has therapeutic potential for tumor immunity. Future perspectives in immunometabolism and antitumor immunity are discussed. Abstract : T cells shape immune responses in cancer, autoimmunity and infection, in which CD4 + T helper (Th) and CD8 + T cells mediate effector responses that are suppressed by regulatory T (Treg ) cells. The balance between effector T cell and Treg cell function orchestrates immune homeostasis and functional programming, with important contributions to the onset and progression of cancer. Cellular metabolism is dynamically rewired in T cells in response to environmental cues and dictates various aspects of T cell function. In this review, we summarize recent findings on how cellular metabolism modulates effector T cell and Treg cell functional fitness in homeostasis and cancer immunity, and highlight the therapeutic implications of targeting immunometabolic pathways for cancer and other diseases.